Kyphotic response alterations in perinatally underfed lactating dams - Salas, Manuel; Ortiz-Valladares, Minerva; Regalado, Mirelta (Revista eNeurobiología, 2022)
Durante la succión las crías reciben alimento, estimulación sensorial para su desarrollo corporal y protección para sobrevivir. En esta revisión se enfatizan las alteraciones en la postura cifótica de madres lactantes F1 con desnutrición perinatal y su expresión durante la succión. En un grupo de ratas gestantes F0 desnutridas (50%, G6-G12; 30%, G13-G19), se evaluó el impacto del ayuno en una incubadora (12 h), y en otro (F1), rotando (12h) entre las camadas a 2 madres lactantes, una con pezones ligados (días 1 al 24 de edad). Destete en el día 25 de edad, seguido por dieta balanceada hasta el día 90, cuando se evaluó su respuesta cifótica. Se cuantificaron (días 5-30 de edad) las dimensiones del cráneo, nariz-coxis, tarso-metatarso y falanges, eje bitemporal, peso corporal y apertura de párpados de las ratas F1. La desnutrición perinatal redujo significativamente el peso corporal, apertura de párpados y déficits del esqueleto, principalmente de la zona de inserción de la masa muscular dorsal toraco-abdominal, participante en la cifosis para lactar. Funcionalmente, esta postura provocó deficiencias del inmunomarcaje c-Fos en la sustancia gris central que controla la musculatura de la región nariz-coxis-falanges de las madres F1 desnutridas para la succión de sus crías (días 4 y 12). Las deficiencias en la respuesta cifótica afectan el desarrollo de las crías con posible daño cognitivo a largo plazo. Los hallazgos pueden ser relevantes para entender las alteraciones en la crianza de madres adolescentes usualmente de talla corta, en el inicio y frecuencia de la alimentación del neonato. Abstract In the rat, the mother provides the newborns with plenty of breastfeeding, sensory stimulation, and protection for survival. In this review, we emphasized the deficits in the kyphotic response of F1 lactating dams with pre- and neonatal undernutrition that interfere with the pups´ sucking activity and physical and brain development. One group (F0) compared the effects of gestational food restriction (50%, G6-G12; 30%, G13-G19) and postnatal undernutrition of F1 pups to investigate their physical development. To analyze the impact of early undernutrition on the physical development of F1 rats, prenatally underfed subjects were placed daily in an incubator (12 h) or by the rotation (12 h) of two dams, one with nipples-ligature (days 1-24) between litters. Weaning was at 25 days old, and rats followed a balanced diet until 90 days, when pregnant F1 dams were tested for the kyphotic response. Skull, nose-coccyx, tarsus-metatarsus, phalange lengths, bitemporal axis, body weight, and eyelid-opening were measured in F1 rats (days 5-30). Pre-and neonatally undernourished F1 subjects exhibited body weight and skeletal deficits at most of the ages than controls. Furthermore, the functional evaluation of the nose-coccyx and limb musculature for the kyphotic posture elicited in F1 mothers by active pups (days 4, 12) indicated that undernutrition interfered with the kyphotic response. Functionally, this posture disrupted c-Fos immunostaining at the periaqueductal gray of F1 dams and the pups´ body growth, brain sensory activity, and possibly later cognition. The findings may be relevant to understand long-term effects in adolescent human mothers, usually with short stature and poor interest in newborn breeding. Keywords: Early undernutrition; physical development; Kyphotic posture, rats.